DAVLAT VA JAMIYAT BOSHQARUV TIZIMDA AYOL RAXBARLARNING TUTGAN O`RNI - Abduhakimova Muslima Bahodir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: this article discusses the role of women in our society today, as well as their role in the economic sphere. The conditions and opportunities created in Uzbekistan for women, the strength of attention to women, gender inequality in the process of reforms carried out today, the opportunities created for the education of women are discussed.